DINAMIKA RESPONS NGO TERHADAP UPAYA PENGEMBANGAN ENERGI TERBARUKAN DI REPUBLIK CEKO - Kurnia Novianti (Jurnal Kajian Wilayah, 2015)
This study focuses on the dynamic responses of some of environmental NGOs in Prague, the Republic of Czech related to the development of renewable energy. Their responses are varied. Some of them support the government policy on renewable energy development, but some others express their disagreement to its policy by demonstration or protest in some media. These responses show that NGOs have their own interpretations and interests about dynamic condition of renewable energy development. They are not always having the same perception with the government policy. They argue that the governments policies somehow contradict with the effort to develop renewable energy in the Republic of Czech. This study itself borrows a resistances perspective to analyze the data and information that were collected through a fild research in Prague. It concludes that the environmental NGOs responses to the effort of renewable energy development are varied based on their methods and strategies inflenced by their ideologies. Keywords: responses, environmental NGO, resistance, renewable energy, the Republic of Czech